P171 LAPAROSCOPIC REPAIR OF A GIANT MORGAGNI'S HERNIA PRESENTING WITH RESPIRATORY DISTRESS. (23rd November 2019) - Davakis, Spyridon; Syllaios, Athanasios; Karydakis, Lysandros; Hasemaki, Natasha; Skotsimara, Antonia; Mylonas, Konstantinos; Tsiboukelis, Antonios; Papalampros, Alexandros; Charalabopoulos, Alexandros
Abstract: Background: Morgagni hernias are a rare entity among diaphragmatic hernias, representing 2% of all cases. Although uncommon, it can be fatal if the diagnosis is missed. Foramen of Morgagni is a triangular space located between the muscular fibers of the xiphisternum and the costal margin fibers that insert on the central tendon of the hemidiaphragm. They usually present in childhood with respiratory symptomatology, and a majority of cases in adults are detected incidentally on chest radiographs. Aims/Scope: To present an extremely rare case of acute dyspnea caused by a giant congenital Morgagni's hernia, together with review the diagnostic algorithm and the role of surgical treatment. Results: A 48-year-old caucasian male, previously healthy, was referred to our department with acute onset dyspnea and vague right-sided chest pain for the past 4 months. No history of chest or abdominal trauma was mentioned. Chest examination revealed bowel sounds and decreased air-entry in the right chest. The patient was offered a laparoscopic repair; at operation, jejunum, ileum, appendix, ascending and transverse colon to its distal two thirds with the associated omentum were found within the hernia sac. Hernia's neck was bridged with a dynamesh IPOM mesh in a tension free manner. The patient is well and symptoms free at 1 year follow up. Conclusion: Majority of Morgagni hernias are diagnosed late because patients are either asymptomatic or present with nonspecific gastrointestinal or respiratory symptoms. Controversy exists regarding operative approaches via either transabdominal route or transthoracic route. In our case, laparoscopic repair was offered with favorable outcome.